2021
DOI: 10.1021/acs.jmedchem.1c01591
|View full text |Cite
|
Sign up to set email alerts
|

Light-Triggered Fluorescence Self-Reporting Nitric Oxide Release from Coumarin Analogues for Accelerating Wound Healing and Synergistic Antimicrobial Applications

Abstract: Nitric oxide (NO) has an important class of endogenous diatomic molecules that play a key regulatory role in many physiological and biochemical processes. However, the type of nitrosamine NO donor stimulated by light has many advantages compared to the conventional NO donors such as diazeniumdiolates and S-nitrosothiols compounds, including easy synthesis, good stability, and controllable release. In addition, NO release can be regulated by light induction with a built-in calibration mechanism fluorescence. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Synthesis of NO photodonors Generally, there are no approaches to predict the efficiency of NO photorelease, and its relation to the molecular structure is not fully understood. Moreover, different mechanisms of NO release were reported, including intramolecular charge transfer (ICT) [34], photoinduced electron transfer (PET) [35], or homolythic fission with the formation of aminium radicals [36]. BODIPY-based N-NO photodonors reported previously [27,28] contain extended linker connecting BODIPY and NO-releasing moiety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of NO photodonors Generally, there are no approaches to predict the efficiency of NO photorelease, and its relation to the molecular structure is not fully understood. Moreover, different mechanisms of NO release were reported, including intramolecular charge transfer (ICT) [34], photoinduced electron transfer (PET) [35], or homolythic fission with the formation of aminium radicals [36]. BODIPY-based N-NO photodonors reported previously [27,28] contain extended linker connecting BODIPY and NO-releasing moiety.…”
Section: Resultsmentioning
confidence: 99%
“…BODIPY-based N-NO photodonors reported previously [27,28] contain extended linker connecting BODIPY and NO-releasing moiety. On the other hand, N-NO group in several cases was directly attached to a chromophore [24,35]. We decided to use short methylene linkage between BODIPY and N-NO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of metal coumarin complexes plays an ideal role in biological activities. Recently, it has been reported that metal and hydroxycoumarin complexes might be applicable as anticoagulants, luminescent for DNA conformation, chemical sensors, and molecular devices [37][38][39][40]. N and S donor ligands greatly enhanced the coordination bonding with metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most prevalent chronic complications of diabetes, diabetic wounds are gaining widespread attention due to their difficulty of healing, and the etiology of this condition frequently results from persistent inflammation and cell dysfunction. 1 Wound repair is a complicated multifactor and multistep process that comprises phases of hemostasis, inflammation, proliferation, and remodeling, 2 and conventional therapies, including debridement, dressing changes and glucose-lowering treatment, do not seem to be effective in the treatment of diabetic wounds. However, newly developed drugs, including basic fibroblast growth factor and vascular endothelial growth factor, only apply to a specific phase of the wound repair process, and their therapeutic effects and clinical applications are also limited.…”
Section: Introductionmentioning
confidence: 99%